Breathable core-shell microneedle patches for diabetic wound treatment - Fan, Lu; Wang, Yu; Wang, Li; Lin, Xiang; Wang, Xiaoju; Shang, Luoran; Zhang, Hongbo; Zhao, Yuanjin (IOP Publishing Ltd, 2025)
Microneedles have demonstrated valuable applications in diabetic wound management. Many endeavors are devoted to developing microneedles with well-designed structures and enhanced functions. Herein, we present an elaborate microneedle patch with breathability for wound healing by a multi-step replication method. The microneedle patch consists of a breathable porous supporting substrate and core-shell tips involving poly (vinyl alcohol) shells loaded with antimicrobial peptides (PVA@AMPs shell) and crosslinked Gelma cores encapsulated with exosomes (Gelma@exo core). The PVA was crosslinked with a ROS-responsive linker, which results in degradation of the microneedle shell in the inflammatory microenvironment, thus inducing the release of loaded AMPs to inhibit bacteria. Further, the exosomes continuously release from the exposed Gelma@exo core, promoting tissue regeneration and regulating the immune response. Besides, the high porosity of the supporting substrate makes the microneedle patches more suitable for chronic wounds. Based on these features, it was demonstrated that the microneedle patch exhibits desirable performance in in vivo animal tests. Thus, we believe that the proposed microneedle patches have remarkable potential in wound healing and related fields.